1982
DOI: 10.1111/j.1470-6431.1982.tb00586.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Relationship Among Wife's Employment Status, Stage in the Family Life Cycle, Meal Preparation Time, and Expenditures for Meals Away From Home

Abstract: The allocation of time is an ultimate reflection of quality of life choices. Since the current trend for increased proportions of dual wage earner families will probably continue, data on how they allocate and consume time will help in clarification of this dual wage earner lifestyle on future consumer decision making and behaviour. Role theory is used to organize data on the relationships between consumption of time in the wives’ provider and homemaker roles. The relationship between purchased services, i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
2

Year Published

1983
1983
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
7
2
Order By: Relevance
“…These findings contradict those of Redman (1980) and Goebel and Hennon (1982) concerning the relationship between age of children and EMPAFH, but support their findings concerning no relationship between mother's employment and EMPAFH. It would appear that a substitution of money for time is not made when the mother spends more time in the wage earner role.…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations
“…These findings contradict those of Redman (1980) and Goebel and Hennon (1982) concerning the relationship between age of children and EMPAFH, but support their findings concerning no relationship between mother's employment and EMPAFH. It would appear that a substitution of money for time is not made when the mother spends more time in the wage earner role.…”
Section: Resultscontrasting
confidence: 65%
“…Rizek and Peterkin (1980) reported that, in 1977, expenses for meals away from home for households where the female head2 was employed 20 or more hours per week averaged $5.80 per household member per week. She also reported, as did Goebel and Hennon (1982), that families with preschool children spent less on meals away from home than other families, and that there is a positive correlation between age of children and allocations for meals away from home. Each away-from-home meal for employed female household heads averaged $2.04, compared to $2.22 for other households.…”
Section: Literature Reviewmentioning
confidence: 73%
See 2 more Smart Citations
“…Some recent research has explored time usage and other variables in two-earner fam-ilies and has produced unanticipated findings. For example, in analyzing food preparation time and expenditures on meals away from home, Goebel and Hennon (1982) found an expected significant decrease in meal preparation time when the wife was employed but not the corresponding expected increase in expenditures on meals away from home. Stafford (1983) did not equate employment status with employment time as is frequently done by researchers.…”
mentioning
confidence: 99%